Mechanical analysis of a wedge device in sawing technology - Mohd Basri, Mohd Salahuddin; Mohd Nor, Mohd Zuhair; Shamsudin, Rosnah (Universiti Putra Malaysia Press, 2019)
The oil palm trunk (OPT) currently represents a massive volume of agricultural waste with great potential to be rapidly developed in the wood composite industry. An improvement in sawing technology has potential to improve the yield of the commercially hard outer core of the OPT by about 27 % thus replacing the present sub-optimal square sawing pattern with a more efficient and higher-yielding polygon sawing pattern. To achieve this, a 'wedge' device was designed to be mounted on the existing sawing carriage. The proper methodology was followed including extraction of the design layout of the machine, development of the schematic drawing and wireframe model, modification of the design in computer-aided design (CAD) environment, the performance of stress, total deformation, and fatigue analysis, and production of a complete drawing for fabrication purpose. Results from the analysis showed that the designed part was safe to be fabricated with a small maximum equivalent stress of 2.546 MPa, maximum total deformation of 0.007935 mm and total life cycle of one million cycles. These evaluation results indicate that the material used for the wedge device (including the base part) satisfies the design requirements of static strength and is safe within its designed fatigue life.